Relaxor behavior of Pb(Fe2/3W1/3)O3 ceramics - Liqin Zhou
The complex perovskite Pb(Fe213W1fi)O; (PFW) is one of the many ferroelectric relaxors. Although PFW has a low transition temperature around 1S5K, it is used to obtain solid solutions with dielectric parameters adjusted to make multilayer capacitors, meeting appropriate standard specifications. PFW was first synthesized in the late fifties, but, it has received less attention than other ferroelectric relaxors, like Pb(Mgl~Nbz5)O; and Pb(Scl~Taii2)03. In this thesis, diierent interesting aspects of the relaxor properties of PFW ceramics, such as synthesis, aging, ordering and disorde~gw, ere studied, in order to extend the understanding of the relaxation behavior of ferroelectric relaxors. PFW ceramics was successfully synthesized by the columbite precursor method, using the reaction between a prereacted columbite-type compound FezW06 and PbO. Considerable improvements were achieved in relation to the conventional mixed oxide procedure: an almost single phase PFW ceramics (>98%), with high dielectric permittivity value (~,,,=12180, at 10KHz) and dense and uniform microstructure, was obtained. The aging behaviors of diierent stoichiometric, Mn and La modified PFW ceramics were studied. The tungsten deficient samples showed evident aging effects, more pronounced as the tungsten deficiency increased. However, lead deficient samples showed no aging phenomena. Mn doping does not cause marked changes in the maximum of the permittivity E,, the transition temperature TO and the diffuseness coefficient 6, while the aging level increases significantly with increasing the Mn content. La doping results in the decrease o, , E, f the shift of To to lower temperatures and the increase of 6. The aging decreases with increasing the La content up to 5at%. No aging was observed at 5at%. Samples doped with lOat% of La show again aging behavior. Comparing with nonstoichiometric and Mn doped PFW ceramics, the aging of La doped samples is not so strong. In general the aging behavior shows a strong dependence on the frequency, a log-linear hnction of the aging time, and a shift of the dielectric distortion with the aging temperature. The defect dipole pairs, provided by the W vacancies, acceptor and donor defects, with the corresponding compensating defects, couple to the polarization vectors, being suggested to be responsible for the aging process of nonstoichiometric, Mn and La modified PFW ceramics. The structural positions of the defects in the perovskite lattice and the reorientation of the defect dipole pairs, were discussed for the studied compositions and suggested to account for the different aging behavior observed between samples with different defective nature. The ordering of PFW ceramics is difficult to be modified by annealing treatments in air, but the presence of vacancies in the ceramics could si@cantly enhance the rearrangement of B cations. Although no superlattice reflections were detected by either X-ray difliaction (XRD) or transmission electron microscopy (TEM) for air annealed samples, considerable modifications of the dielectric properties were observed after air annealing treatment: the dfiseness of the dielectric permittivity is decreased and the permittivity maximum value is increased. The annealing effect is enhanced with increasing the amount of Mn dopant; it weakens with increasing the La content below 5at%, and the dielectric permittivity and loss factor are almost unchanged after annealig a 5at% La doped sample. Further increase in La content, leads to the annealing effect becoming evident again. The role of the oxygen and lead vacancies, present in Mn and La doped PFW ceramics, respectively, on the annealing process, was proposed and discussed. Sodium doping could easily moe the ordering of PFW ceramics. The superlattice reflections, indexed as {h+i, k+i, 1++ }, were observed in both XRD and TEM diiaction patterns. These reflections were identified to be associated with 1:l type ordering of B cations. The ordering degree increases with increasing the Na content, when NalXat% and decreases, when Na>Xat%. The Na modified PFW ceramics were not single phase. Besides the PFW perovskite phase, a second phase, PbW04, was also observed and its amount increases with increasing the Na content. The effect of the sodium substitutional ions, on enhancing the ordering of the PFW ceramics, was suggested to be due to the weakening of the charge effect, in the ordered regions, caused by the lower valence of Na+ ions, when substituting pb2* ions. The competition between the enhancement of ordering and the formation of PbW04 phase was suggested to be responsible for the decrease of ordering when Na>Xat%. La doping causes a decrease of ordering of PFW perovskite. The effects of Na and La doping on the dielectric properties were also analyzed and discussed. The relaxation behavior of the PFW ceramic compositions studied in this work supports the compositional fluctuation and superparaelectric models proposed to explain the dielectric diffuseness of ferroelectric relaxors.